ACADEMIC STUDY OF DISTRICT FORMATION SOUTH INDRAGIRI - Satriawan Fikri, Novyar; Azhar, Ali (Progressive Law Review, 2020)
This research is motivated by the geographical conditions of Indragiri Hilir Regency in the Southern Region of Riau Province with an area of + 18,812, 97 km2, the vast area of Indragiri Hilir Regency coupled with the condition of almost 80% of the territorial waters which causes a range of spite and the difficult distance of the community with Central government. This type of research belongs to the type of Observational Research legal research by survey. the formation of new autonomous regions will increase the cost of administering government, but is expected to improve the quality and equity of services to the community, increase the acceleration of economic development, especially in rural areas, facilitate the growth of democratic life in the regions, improve security and order in the regions, contribute to unity and nationality (nation building). Keywords